Analisis Kebijakan E-Government Berbasis Ekonomi Digital: Studi Kasus Aplikasi E-Peken di Kota Surabaya - Gunadewa Kusuma, Rayhan (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to evaluate the implementation of e-government through the E-Peken application developed by the Surabaya City Government, using the five-stage e-government evaluation model by the United Nations: Emerging, Enhanced, Interactive, Transactional, and Connected. E-Peken serves as a digital platform to support the promotion and transaction of local MSME products. This research employed a descriptive qualitative method with data collected through interviews, observation, documentation, and literature review. The findings indicate that E-Peken is in a transitional phase between the Enhanced and Interactive stages but has not yet met the criteria for the Transactional and Connected stages. Major limitations are identified in terms of interactivity, inter-agency integration, and the availability of comprehensive digital transaction services. Furthermore, the absence of data interoperability and analytics-based reporting systems poses challenges to achieving integrated e-government. This study recommends strengthening digital infrastructure, cross-agency system integration, development of end-to-end transaction features, and digital literacy training for MSME actors. The findings are expected to provide strategic input for the Surabaya City Government in developing more effective, participatory, and sustainable technology-based public services. Keywords: E-Government, E-Peken, UMKM